Neoliberal economics, planetary health, and the COVID-19 pandemic: a Marxist ecofeminist analysis (2020)
Planetary health sees neoliberal capitalism as a key mediator of socioecological crises, a position that is echoed in much COVID-19 commentary. In this Personal View, I set out an economic theory that emphasises some of the ways in which neoliberal capitalism’s conceptualisation of value has mediated responses to COVID-19. Using the intersection of ecological, feminist, and Marxist economics, I develop an analysis of neoliberal capitalism as a specific historical form of the economy. I identify the accumulation of exchange value as a central tendency of neoliberal capitalism and argue that this tendency creates barriers to the production of other forms of value. I then analyse the implications of this tendency in the context of responses to COVID-19. I argue that resources and labour flow to the production of exchange value, at the expense of production of other value forms. Consequently, the global capitalist economy has unprecedented productive capacity but uses little of this capacity to create the conditions that improve and maintain people's health. To be more resilient to coming crises, academics, policy makers, and activists should do theoretical work that enables global economies to recognise multiple forms of value and political work that embeds these theories in societal institutions.